Creative Thinking Skills based on Self-efficacy in Creative Problem Solving Learning with Scaffolding - Muti'ah, Umi; Waluya, St. Budi; Mulyono, Mulyono (IJECA (International Journal of Education and Curriculum Application), 2022)
This research aimed to discuss creative mathematical thinking ability based on self-efficacy in CPS learning with scaffolding. This research employed qualitative descriptive design. The subjects of the research were 6 students of class XI of junior high school selected based on three categories of self-efficacy, they were: high, medium, and low. Two students were found in the high self-efficacy category, two students from the medium self-efficacy category and two students from the low self-efficacy category. The results of this research showed that students with high self-efficacy level were able to complete the four qualifications of creative thinking abilities, they were fluency, flexibility, originality, and elaboration. Students with the medium self-efficacy level were still having difficulty showing up ideas to determine the unusual way of being used. Students with low self-efficacy level had difficulty in understanding the problem so that it is only able to meet one qualification of creative thinking ability that is fluency. Based on the explanation of the results of this research, it can be concluded that no student with low self-efficacy level has a high score of creative thinking ability.